Prevalence of acne in primary school children and the relationship of acne with pubertal maturation - DEMİRCİOĞLU, SERAP (DERI ZUHREVI HASTALIKLAR DERNEGI, 2014)
Background and Design: Although acne vulgaris is generally regarded as a disease of adolescence period, it can occur in infancy, early childhood and prepubertal period. Acne may emerge as the first sign of pubertal maturation. In our study, we aimed to determine the acne prevalence in primary school children, then, evaluate the pubertal signs in those children; examine the correlation of the presence and severity of acne with pubertal signs, and finally, revise the concept of prepubertal acne. Materials and Methods: A thousand students from 2 schools in Istanbul were included in the study. Age, gender, and the presence, localization and severity of acne were recorded. Acne severity was evaluated using the Orfanos-Gollnick Acne Grading System while a validated self evaluation form which had been developed by Morris and Udry was used to evaluate pubertal stage. Data were evaluated statistically. Results: Five hundred and thirty-four male and 466 female primary school children, with an age range of 7 to 11, were included in the study. Acne was determined in 11.5% of the students. 20% of girls and 4% of boys had acne. Comparing acne presence and age, the average age was higher in group with acne than those with no acne. The mean age of children with grade 1 acne was lower than those with grade 2 acne. All the students with acne had mid-facial acne. Comparing acne presence and pubertal symptoms, the rate of the presence of acne was higher in pubertal girls. No acne was observed in prepubertal boys. Evaluating acne severity and pubertal signs, the difference between prepubertal and pubertal girls was not significant. Comparing acne and telarche stages, the group without acne had lower telarche rates. Comparing acne and pubertal stages, children with acne had advanced puberty. Conclusion: Our study denotes that acne prevalence is related to pubertal maturation and age; while it does not support the hypothesis that acne is the first sign of pubertal development.
Keywords: Acne; puberty; childhood; CHILDHOOD ACNE; SKIN CONDITIONS; DIET; DISORDERS; VULGARIS